Production of bikaverin by a Fusarium fujikuroi mutant in submerged cultures - Lale, Geetanjali; Gadre, R. V. (AMB Express, 2016)
A variety of mutants having different colony characteristics, morphology and soluble pigmentation were generated from Fusarium fujikuroi by exposure to UV radiation. Mutants were selected that formed dry, compact, small colonies with reddish-violet pigment on regeneration agar plates. The production of bikaverin by Mut-4 was examined in shake flasks in media with different nitrogen and carbon sources. The optimal C: N ratio for the maximal bikaverin production by Mut-4 was 150: 1. It produced still higher bikaverin (6.3 g l(-1)) in a medium containing defatted cottonseed meal as nitrogen source, in combination with glucose. Bikaverin produced was extracted, purified and characterized by UV-visible and NMR spectroscopy. Bikaverin production in the present investigation was substantially higher than that reported by earlier investigators in submerged and solid-state fermentations.
Keywords: Bikaverin; Fusarium fujikuroi; Gibberella fujikuroi; Pigment production; Submerged cultures